Assessing the coral microbiome at the scale of tissue-specific habitats within the coral meta-organism - Bergman, Jessica L.; Shaw, Tayla; Egan, Suhelen; Ainsworth, Tracy D. (Frontiers in Marine Science, 2022)
As sequencing techniques have advanced and become cheaper in recent years, there has been a rapid increase in the number of studies conducted into the role of the microbiome in coral health, physiology, and response to environmental change. However, there is substantial variation in the methodological approaches applied. For example, DNA extraction protocols and the types of tissues sampled from the coral meta-organism are known to influence the downstream analyses of the amplified microbial communities and subsequently the interpretation of the microbiome diversity, stability and role. Studies have generally focused on whole organisms, in which the coral sampling steps homogenize the meta-organism microhabitats, however other studies targeting specific microhabitats have identified sources of variation specific to distinct compartments of the coral’s microbial landscape. Here we present a comparative analysis of methodologies optimized for the generation of coral microbiome data from the coral tissues and whole coral fragments of two commonly studied branching coral genera with distinct tissue structure. We investigate the microbiome of the imperforate Pocillopora, where the coral tissue does not penetrate through the calcium carbonate matrix, and the perforate Acropora, where the coral tissues and skeleton are interwoven throughout the coral branch. Through comparing data generated from different DNA extraction protocols using fixed coral tissues isolated from the coral skeletal structure with fixed whole coral fragments, we identify sources of variation inherent to microbial data generated from different sample types, species, and extraction protocols.